Palestinians in Syria : Nakba Memories of Shattered Communities - Al-Hardan, Anaheed (Columbia University Press, 2016)
Based on interviews with first-, second-, and third-generation members of Syria's Palestinian community, this book challenges the nationalist and patriotic idea of the Nakba's memory as static and universally shared. Following the evolution of the Nakba in Syria and its transformation in the country's Palestinian politics, this study sheds light on the enduring relevance of the Nakba among the communities it helped create, as well as its changing meaning in light of the Syrian war.